Pemikiran Pendidikan Islam Abu Hasan Ali Bin Muhammad Al-Qabisi - Firman; Anwar Saputra, Chairul (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to determine the thoughts of Islamic education according to Al-Qabisi and his contribution to Islamic education. Al-Qabisi was a prominent educational figure around the 4th century Hijri, his concept of thought became a reference in teaching children at that time. Al-Qabisi's thoughts on Islamic education include children's educational institutions, the goals of Islamic education, the Islamic education curriculum consisting of the ijbari and ikhtiyari curriculum, methods and learning techniques. In addition, Al-Qabisi also criticized the world of educators or teachers, the separation between male and female students, the prohibition of non-Muslims studying in kuttab owned by Muslims and so on. Al-Qabisi had a concept of evaluation, although it was not like the concept and evaluation system today. Al Qabisy's contribution to improving the quality of Islamic education can be seen in improving the quality of religious education and the Islamic education system. He argued that religious education should be the basis for Islamic education.